Captain Cook's third and last voyage to the Pacific Ocean [electronic resource] : in the years 1776, 1777, 1778, 1779 and 1780. - Cook, James, 1728-1779; King, James, 1750-1784. (London : Printed for John Fielding . and John Stockdale, 1785)
Abridgement of A voyage to the Pacific Ocean / James Cook and James King. "Faithfully abridged from the quarto edition. Illustrated with Copper Plates." Electronic reproduction. Mode of access: Internet. 44